Potensi Kombucha Sebagai Minuman Probiotik Dan Sumber Antioksidan - Putri, Aisya Kamila; Sabrina, Sabrina (Jurnal Ilmiah Wahana Pendidikan, 2024)
Excessive free radicals can lead to detrimental oxidative stress. Low antioxidant activity can trigger health issues like metabolic disorders and cell degeneration. Kombucha is the product of tea and sugar fermentation by a symbiosis of bacteria and yeast, offering benefits such as antioxidants, antibacterial properties, and immune support. The goal of this study is to explore the potential of kombucha as a probiotic beverage rich in antioxidant properties. A literature review of 8 research articles on antioxidant activity in kombucha was conducted. Articles were obtained through Google Scholar and the Garuda portal using the keyword "antioxidant activity kombucha," with a time span of the past 5 years. Screening was based on titles, abstracts, and full article contents, including background, methods, results, discussions, and conclusions. Kombucha exhibits varying levels of antioxidant activity, dependent on the phenolic composition of the beverage. Several studies indicate that kombucha made from ingredients such as cocoa leaves, green tea, cherry leaves, ginger, and pennywort has high antioxidant activity. Kombucha has the potential to be a beverage rich in antioxidants, contributing to combating oxidative stress and preventing degenerative diseases.